2021
DOI: 10.1088/1748-605x/ac11ca
|View full text |Cite
|
Sign up to set email alerts
|

Solution blow spinning of PLLA/hydroxyapatite composite scaffolds for bone tissue engineering

Abstract: Composite poly-L-lactide acid-based scaffolds with hydroxyapatite (HAp) content up to 75 wt.% were fabricated via solution blow spinning. The influence of HAp concentration on structure, wettability, mechanical properties and chemical and phase composition of the produced materials was examined. It was found that with an increase of HAp content the average fiber diameter was increased, the uniaxial strength and relative elongation were reduced, while the phase composition and surface wettability did not change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The authors of Reference [65] found that adding hydroxyapatite (HAp) to Composite poly‐ l ‐lactide acid (PLLA)‐based scaffolds reduced its thermal stability. It was reported that particles of HAp powder in composite scaffolds based on PLLA obtained using the SBS method stimulated thermal destruction of the polymer matrix 65 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of Reference [65] found that adding hydroxyapatite (HAp) to Composite poly‐ l ‐lactide acid (PLLA)‐based scaffolds reduced its thermal stability. It was reported that particles of HAp powder in composite scaffolds based on PLLA obtained using the SBS method stimulated thermal destruction of the polymer matrix 65 …”
Section: Resultsmentioning
confidence: 99%
“…84 In Figure 5b, one can observe that with the incorporation of nanofibers into the NR matrix, the most intense degradation peaks shift to higher temperatures. The authors of Reference [65] found that adding hydroxyapatite (HAp) to Composite poly-Llactide acid (PLLA)-based scaffolds reduced its thermal stability. It was reported that particles of HAp powder in composite scaffolds based on PLLA obtained using the SBS method stimulated thermal destruction of the polymer matrix.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Scalable methods for fabricating such materials include but are not limited to electrospinning and solution blow spinning (SBS) 2 . The unique properties of nano‐ and submicron fibrous materials, like the high specific surface area, high porosity, good mechanical properties, and structural characteristics associated with their size, make them candidates as building materials for various products, including smart materials, through energy and catalysis applications, materials for environmental protection to biomedical applications 3–13 …”
Section: Introductionmentioning
confidence: 99%
“…2 The unique properties of nano-and submicron fibrous materials, like the high specific surface area, high porosity, good mechanical properties, and structural characteristics associated with their size, make them candidates as building materials for various products, including smart materials, through energy and catalysis applications, materials for environmental protection to biomedical applications. [3][4][5][6][7][8][9][10][11][12][13] The spinning of polymer solutions to the fibrous materials requires an interplay between specific solution properties and processing parameters regardless of the applied technique. 14 Determining the values of the processing parameters and the determination of polymer solution properties remains a significant challenge, especially in new processes like the SBS.…”
Section: Introductionmentioning
confidence: 99%